2007
DOI: 10.2116/analsci.23.1015
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Neurosteroids XXI: An Improved Liquid Chromatography–Tandem Mass Spectrometric Method for Determination of 5α-Androstane-3α,17β-diol in Rat Brains

Abstract: A sensitive liquid chromatography-electrospray ionization-tandem mass spectrometric (LC-ESI-MS/MS) method for the determination of the rat brain 5α-androstane-3α,17β-diol (3α,5α-Adiol) has been developed and validated. The brain extract was purified using solid-phase extraction cartridges, derivatized with isonicotinoyl azide, and subjected to LC-MS/MS. The method was accurate and reproducible, and the limit of quantitation was 0.1 ng/g tissue when a 100-mg tissue sample was used. The change in the brain 3α,5α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To characterize the physiological function of 5a-androstane-3a,17b-diol (3a,5a-Adiol), a metabolite of testosterone (T), and the mechanism by which it affects the brain function, isonicotinoyl azide derivatization and LC-MS/MS were applied to analyze changes in the steroid levels by immobilization stress (Higashi et al, 2007a).…”
Section: Derivatization-based Lc-msmentioning
confidence: 99%
“…To characterize the physiological function of 5a-androstane-3a,17b-diol (3a,5a-Adiol), a metabolite of testosterone (T), and the mechanism by which it affects the brain function, isonicotinoyl azide derivatization and LC-MS/MS were applied to analyze changes in the steroid levels by immobilization stress (Higashi et al, 2007a).…”
Section: Derivatization-based Lc-msmentioning
confidence: 99%
“…Although earlier studies on brain steroid concentrations analyzed by RIA or GC-MS have shown relatively high levels for these compounds, other reports based on more direct measurement using a LC-MS/MS method found substantially lower concentrations in brain tissue [9,39] [40][41][42][43][44]. The challenge for the LC-MS/MS quantification of unconjugated steroids rests on sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 96%
“…6,11) The mean steroid concentrations with standard deviations of the respective groups (nϭ10) are shown in Figs. 2a and b.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Industries (Osaka, Japan). The derivatization reagents, isonicotinoyl azide (INA) 6) and 2-hydrazino-1-methylpyridine (HMP), 9) were synthesized in our laboratories. Strata-X (60 mg adsorbent) and Bond Elut Si (500 mg adsorbent) cartridges were purchased from Phenomenex (Torrance, CA, U.S.A.) and Varian (Harbor, CA, U.S.A.), respectively.…”
Section: Materials and Reagentsmentioning
confidence: 99%